Education and Growth in the Presence of Capital Flight - Debajyoti Chakrabarty; Areendam Chanda; Chetan Ghate (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
We study the effect of capital controls on the level of investment in human capital and the resulting growth path of an economy. The economy consists of two groups of agents based on the ownership of factors of production. One type of agents – called workers – own human capital and bequeath education to their offsprings. The other group of agents – called capitalists – own and bequeath physical capital. The workers have the political power to tax capital income. The capitalists, based on the tax rate imposed by the workers and the capital control regime in place, decide to invest part or all of their capital abroad. We characterize the optimal tax behavior of the workers. We find that higher capital controls are beneficial for investment in education whenever there is capital flight in a steady state equilibrium. However, higher capital controls are shown to have no effect on the tax rate on capital income imposed by workers: rather, they act as a disincentive for capital flight by lowering the return from foreign investment. We show that lowering capital controls can lead to higher growth only when there is no capital flight in the steady state. Importantly, to prevent capital flight in the long run, human capital accumulation must not show decreasing returns with respect to education and the economy must be sufficiently developed.
Keywords: 330